(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Violence among young people is a growing concern worldwide, often leading to physical harm, psychological damage, and social instability. This article explores the various means of preventing violence among youth, focusing on early intervention strategies, education, social support systems, and the role of parents and schools. Through literature analysis and case studies, effective methods for violence prevention are identified, along with suggestions for policy improvements to address this issue.